The next generation of Chinese investment treaties: A balanced paradigm in an era of change - Qianwen Zhang (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
China's Foreign Investment Law reflects substantial changes in China's foreign investment legal regime. This Perspective discusses two new characteristics of the new generation of Chinese investment treaties: they are based on a balanced paradigm and they are becoming more influential at the domestic level.
Keywords: 330